Microsoft Exchange 2003 deployment and migration - McCorry, Kieran, 1968- (Amsterdam ; Boston, Mass. : Elsevier Digital Press, 2004)
Microsoft® Exchange Server 2003 Deployment and Migration describes everything that you need to know about designing, planning, and implementing an Exchange 2003 environment. The book discusses the requisite infrastructure requirements of Windows 2000 and Windows 2003. Furthermore, this book covers, in detail, the tools and techniques that messaging system planners and administrators will require in order to establish a functioning interoperability environment between Exchange 2003 and previous versions of Exchange including Exchange 5.5 and Exchange 2000. Since Microsoft will drop support for Exchange 5.5 in 2004, users will have to migrate to Exchange 2003. Additionally the book describes various deployment topologies and environments to cater for a multitude of different organizational requirements. * Details for consultants and system administrators to migrate from older versions of Exchange 5.5 and Exchange 2000 * Critical information on integration with Outlook 2003 and Windows 2003 * Based on actual implementations of both beta and final release versions of Exchange 2003 in larger enterprise environments.
Includes index.
Keywords: Microsoft Exchange; Client/server computing; Electronic mail systems; Electronic books